Development of a quantitative system for subjective evaluation of tracked vehicle crew jackets - Hee Eun Choi; Youngshil Ryoo; Kuengmi Choi (Fashion and Textiles, 2022)
Abstract The purpose of this study is to develop a quantitative evaluation system that reflects the required performance factors that are important for a tracked vehicle crew jacket. We identified and analyzed the necessary performance factors obtained from a focus group interview and a questionnaire survey. Further, we proposed a new method of calculating weights and developed a quantitative evaluation system. This system featured an equation that calculated the evaluation score out of 100, using the factors’ percentages in the total factor as factor weights. The system’s application was verified by the assessment of subfactors by active-duty soldiers, and by confirmation that the results of the developed factor scores reflected the proposed development direction. The study is significant for its provision of a comprehensive and quantitative evaluation system which has not existed before for protective clothing design, as well as for the verification of the system’s application through the process of protective clothing development. The quantitative evaluation system and its development process described in this study may be referenced and widely deployed due to its use of a Likert scale, which is commonly used as a subjective sensory evaluation tool.